Agroforestry experiences and agrecological transition: from conventional to organic at Farm Vale das Palmeiras Orgânicos - RJ (Research, Society and Development, 2023)
This study intends to discuss and analyze the process of Agroecological Transition (AT) towards sustainability based on the systematization of the experience of Fazenda Vale das Palmeiras Orgânicos (FVPO), in the municipality of Teresópolis - RJ. Agroforestry knowledge takes place through exchange spaces that are formed by experimentation; in solidarity, interacting and experimenting through reflections on the dialogue of experiences and agroecological practices, contributing to its recognition, strengthening and consolidation. Since 1997, FVPO has become a promoter and promoter of the agroforestry proposal that serves from farmers, technicians, and students to the public. The experiences acquired in this space provide theoretical and practical training, bringing knowledge in several areas, highlighting the pedagogical, technical, productive, and economic areas. The experiences of an agroforestry with twenty-six years of management and AT made the farm a reference for agroforestry dissemination. The methodology of this action-research was presented in a descriptive and qualitative review research that was a review study. To succeed in the AT process, combined actions are needed that require initiatives between civil society groups and institutions such as public authorities so that these interventions influence the processes of social production and sustainable development, and collaboration with other ongoing AT processes at local and regional levels. The improvement in production can help in innovative strategies such as the development of products without pesticides, providing substantial benefits to the population.